Penentuan Kadar Merkuri (Hg) pada Kerang Hijau (Perna viridis) di Pasar Serpong Menggunakan Mercury Analyzer Metode Direct Thermal Decomposition - Utha Rosalita Permata Putri; Rina Rismaya (LPPM Universitas Terbuka, 2023)
Green mussels (Perna viridis) can accumulate heavy metals from their environment. In the biota’s living cells, heavy metals can be accumulated and if consumed, could have an adverse effect on human health. Mercury (Hg) is one of heavy metals that usually pollute river water. This study aimed to quantify the mercury level of heavy metals in green mussels and the results were compared to the provisions in SNI 7387:2009 on the maximum limit of heavy metal contamination in food. The mercury analyzer with the direct thermal decomposition technique with a wavelength of 253.7 nm was used to measure the mercury levels in green mussels. The green mussel sample was obtained from several seller in Pasar Serpong. Green mussel was found to be taken from the coast of Tangerang regency river that was indicated to be polluted by heavy metals. The analysis was done using the standard series, which yielded a correlation coefficient (r) of 0.9997 and a percentage recovery of 102.65%. The results showed that three analysed samples met the Mercury metal quality criteria. The three samples of green mussels sold on Serpong Market was deemed to be safe for human consumption.